Pengembangan Modul Fisika Berbasis OASIS Pada Materi Suhu dan Kalor Untuk Meningkatkan Kemampuan Berpikir Kritis - Rice Yanita Dian Christi; Jeffry Handhika; Andista Candra Yusro (Universitas Muhammadiyah Purworejo, 2020)
This research aims to improve critical thinking skills by developing OASIS-based modules. The stages of the OASIS Model include concept orientation, concept analysis, concept synthesis, concept investigation and concept synergy. This type of research is development research. The subjects of the study were students of class X MIPA 1 of SMA Negeri 1 Jiwan, Madiun Regency. Data collection techniques were carried out by the method of tests, observations, and questionnaires. Data analysis techniques used the Likert scale and the Guttman scale for the questionnaire and t-test for the test method. Product validation based on 4 aspects namely linguistic, content eligibility, OASIS assessment and presentation of material for material experts and 3 aspects namely module size, cover design, and content design for media experts. Based on the validation results of the developed learning module material, an average rating of 69.6% can be obtained with reasonable criteria (with revisions) and media experts obtained an average rating of 80% with decent criteria. N-Gain results from pretest and posttest obtained an average of 0.35 so as to get a moderate criterion (the ability to think critically increases). Thus the learning modules that have been developed are worthy of being used as teaching materials in learning physics in the Temperature and Heat material and can improve students' critical thinking skills.